2009
DOI: 10.1007/s00213-009-1692-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of glucose tablets to aid smoking cessation

Abstract: No significant effect of glucose tablets over and above sweet tasting tablets could be detected overall, but the possibility of an effect as an adjunct to NRT or bupropion merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Dear Editor, West et al (2010) reported that glucose tablets alone were no better than placebo in helping smokers to quit (11% vs 14%). However, among smokers also using an approved smoking cessation medicine (nicotine replacement or bupropion), glucose tablets increased their 6-month quit rate (18.2% vs 12.6%, p<0.05).…”
mentioning
confidence: 96%
“…Dear Editor, West et al (2010) reported that glucose tablets alone were no better than placebo in helping smokers to quit (11% vs 14%). However, among smokers also using an approved smoking cessation medicine (nicotine replacement or bupropion), glucose tablets increased their 6-month quit rate (18.2% vs 12.6%, p<0.05).…”
mentioning
confidence: 96%
“…It was hypothesised that glucose tablets could promote abstinence by satiating carbohydrate cravings that ex-smokers often mislabelled as cigarette cravings [146,147]. Previous studies have shown that nicotine acts as an acute appetite suppressant by raising blood glucose levels and acting directly on cells in the lateral hypothalamus.…”
Section: Glucose Tabletsmentioning
confidence: 99%
“…In a randomised controlled trial with nearly one thousand participants, no significant effect of glucose tablets over and above sweet tasting tablets was detected [147]. However, glucose tablets may promote short-term abstinence, particularly when used as an adjunct to NRT or bupropion [147,148].…”
Section: Relative Efficacymentioning
confidence: 99%
See 2 more Smart Citations